2005
DOI: 10.1016/j.jmwh.2005.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Level and Perinatal Outcome in Pregnant Women With Posttraumatic Stress Disorder: A Pilot Study

Abstract: Posttraumatic stress disorder (PTSD) affects 12% of women in the United States and could affect childbearing via behavioral and neuroendocrine mechanisms. This pilot study collected preliminary data about the extent to which the low cortisol profile found in patients with PTSD also occurs in the hormonal context of pregnancy, as well as the association between PTSD and less optimal processes and outcomes of pregnancy. Standardized psychiatric diagnostic telephone interviews, salivary cortisol assays, and medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…(2011) find no differences in salivary cortisol concentrations based on pregnancy or non-pregnancy related distress, and Voegtline et al (2013) find that self-report of mental distress is not associated with significant variation in salivary cortisol among pregnant women. Data from our studies of pregnant women, including findings from this data set published elsewhere (Seng et al, under review) and previous preliminary work (Seng, Low, Ben-Ami, & Liberzon, 2005), have found flatter diurnal curves among women with PTSD (i.e., lower morning peak and higher late afternoon and bedtime levels). Obel et.…”
Section: Introductionsupporting
confidence: 55%
“…(2011) find no differences in salivary cortisol concentrations based on pregnancy or non-pregnancy related distress, and Voegtline et al (2013) find that self-report of mental distress is not associated with significant variation in salivary cortisol among pregnant women. Data from our studies of pregnant women, including findings from this data set published elsewhere (Seng et al, under review) and previous preliminary work (Seng, Low, Ben-Ami, & Liberzon, 2005), have found flatter diurnal curves among women with PTSD (i.e., lower morning peak and higher late afternoon and bedtime levels). Obel et.…”
Section: Introductionsupporting
confidence: 55%
“…Finally, in a small prospective pilot study of 25 women, 10 with PTSD, researchers found that number of PTSD symptoms was significantly negatively correlated (r=−0.725) with the Optimality Index-US, a combined measure of 52 dichotomous antenatal and postnatal events (Seng et al 2005). Although the focus of this report was specifically preterm delivery, the study supports a higher general risk of birth complications among pregnant women with PTSD.…”
Section: Discussionmentioning
confidence: 58%
“…A pilot study with 25 subjects did determine that women who experienced PTSD had lower basal salivary cortisol levels but they did not examine pregnancy outcomes [8].…”
Section: B1 Backgroundmentioning
confidence: 99%